2000
DOI: 10.1038/35048589
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of FGF signalling in mouse β-cells leads to diabetes

Abstract: Fibroblast growth factor (FGF) signalling has been implicated in patterning, proliferation and cell differentiation in many organs, including the developing pancreas. Here we show that the FGF receptors (FGFRs) 1 and 2, together with the ligands FGF1, FGF2, FGF4, FGF5, FGF7 and FGF10, are expressed in adult mouse beta-cells, indicating that FGF signalling may have a role in differentiated beta-cells. When we perturbed signalling by expressing dominant-negative forms of the receptors, FGFR1c and FGFR2b, in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
187
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 217 publications
(204 citation statements)
references
References 25 publications
12
187
1
1
Order By: Relevance
“…However, the effects and mechanisms of metformin on FGFR1 have not been fully elucidated and further research is required. Previous study has shown that pancreatic and duodenol homeobox 1 (PDX1) is required for the expression of FGFR1 in the pancreas and metformin could induce PDX1 in embryonic pancreas [14]. Since PDX1 involves in the development and functions of β cells [14], the normalization of FGFR1 after metformin treatment may indicate the improved functions of β cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the effects and mechanisms of metformin on FGFR1 have not been fully elucidated and further research is required. Previous study has shown that pancreatic and duodenol homeobox 1 (PDX1) is required for the expression of FGFR1 in the pancreas and metformin could induce PDX1 in embryonic pancreas [14]. Since PDX1 involves in the development and functions of β cells [14], the normalization of FGFR1 after metformin treatment may indicate the improved functions of β cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study has shown that pancreatic and duodenol homeobox 1 (PDX1) is required for the expression of FGFR1 in the pancreas and metformin could induce PDX1 in embryonic pancreas [14]. Since PDX1 involves in the development and functions of β cells [14], the normalization of FGFR1 after metformin treatment may indicate the improved functions of β cells. Besides, gen analysis suggested that FGFR1 may be a regulator of adipogenesis by increasing fat cell numbers [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CRH secretion by the paraventricular nucleus of the hypothalamus is one of the first steps in the mammalian stress response. Hart et al (19) perturbed FGFR1 dominant-negative signaling in the mouse pancreas and observed a phenotype typical of type 2 diabetes. They demonstrated that mice with attenuated FGFR1 signaling developed diabetes with age, exhibited decreased numbers of ␤-cells, and had increased proinsulin content in ␤-cells.…”
mentioning
confidence: 99%
“…171 185,186 and, to a limited extent, TGF-a, 179,187,188 can promote pancreatic cell growth and islet cell proliferation. Hart and co-workers 189,190 colleagues have produced evidence suggesting that fibroblast growth factor (FGF) signalling is important for b-cell generation. 189,190 Strategies aimed at engineering b-cell progenitors from pancreatic ductular epithelium with FGF in the presence of a permissive PDX-1 expression could promote expansion of b-cell progentors or a differentiation of progenitors into a pre-b-cell lineage.…”
Section: Stem/progenitor Cellsmentioning
confidence: 99%